Application of Sprint Exercises to Student Long Jump Performance - Ikadarny, Ikadarny; Syafruddin, Muhammad Akbar (JOURNAL RESPECS (Research Physical Education and Sports), 2025)
This study uses experimental methods with pre-test and post-test designs. The subject of the study is students who are taking athletic courses in the Physical Education, Health, and Recreation Study Program. A total of 30 students were selected by purposive sampling based on certain criteria, such as healthy physical condition, basic ability to jump long jump, and willingness to participate in training programs consistently. Data analysis was carried out using a paired sample t-test statistical test to determine the significant difference between the pre-test and post-test results. The results of the hypothesis test using the Paired Sample T Test are known to have a mean value of 4.3 pre-test data, a mean value of post-test data of 4.9, with a mean difference of 0.6, so it can be said that sprint exercises are able to improve students' long jump skills. Furthermore, based on the results of the study, it is known that the Sig. value is 0.000 or < 0.05, so it can be concluded that there is a difference in the data of pre-test and post-test students' long jump ability. Based on the results of the research and data analysis, it can be concluded that sprint exercises are proven to be effective as a method to improve students' long jump ability.